Biomechanics of aerial righting in wingless nymphal stick insects. Issue 1 (6th February 2017) - Zeng, Yu; Lam, Kenrick; Chen, Yuexiang; Gong, Mengsha; Xu, Zheyuan; Dudley, Robert
Abstract : Numerous wingless arthropods as well as diverse vertebrates are capable of mid-air righting. We studied the biomechanics of the aerial righting reflex in first-instar nymphs of the stick insect Extatosoma tiaratum . After being released upside-down, insects reoriented dorsoventrally and stabilized body posture via active modulation of limb positions and associated aerodynamic torques. We identified specific reflexes for bilaterally asymmetric leg displacements which elicit body rotation and subsequently stabilize mid-air posture. Coordinated appendicular movements thus improve torsional manoeuvrability in the absence of wings, as may have characterized the initial origins of controlled aerial behaviour in arthropods. Design of small aerial or multimodal robotic vehicles may similarly benefit from use of such strategies for flight control.